Indigenous Psychology Suryomentaram: Urgency and Introduction to Javanese Literary Ethnopsychology - Dhoni Zustiyantoro; Agus Nuryatin; Teguh Supriyanto; Mukh Doyin (Universitas Negeri Semarang, 2021)
This research is a preliminary study to examine the psychology of Suryomentaram (Suryomentaram, 1985a, 1985b) as a theory in Javanese literary research. The purpose of this study was to compare Suryomentaram's thoughts with Western psychological thinkers. So far, psychological research in Javanese literature uses Sigmund Freud's theory, which carries id, ego, and superego (Milner, 1992). The results of research studies show that the structure of literary works and psychological symptoms is only seen as a building structure of Javanese literature. Literary works need to be studied with a local approach to understanding their social and cultural context. The results of this study indicate the weaknesses of Javanese literary psychology research, compare the psychology of Suryomentaram with the West theorists, namely Sigmund Freud, Carl Gustav Jung, and Alfred Adler, and offer Suryomentaram's psychology as an approach to Javanese literary research. Suryomentaram teaches psychological concepts originating from Javanese culture, namely kramadangsa, mawas diri, and rumaos leres.